Analysis Of Easturn Coffee Business Model Design With Business Model Canvas Approach - Muhammad Abidzar Gathan Falaah; Sunu Puguh Hayu Triono (Journal of Indonesia Business Research (JIBR), 2025)
Easturn Coffee is a cafe that provides a comfortable place to enjoy food and drinks. Easturn Coffee is located at JalanCilangkap Baru No. 1 Blok B, RT.3/RW.1, Cilangkap, Kec. Cipayung, East Jakarta City, Special Capital Region of Jakarta.This cafe provides a variety of interesting food and drink choices, a variety of coffee variants are offered so that consumerscan enjoy the taste of quality coffee beans. Easturn Coffee has a major problem in its business, namely a small marketsize and unstable income. So the author conducted this study with the aim of finding out the competitive strategy currentlyimplemented by Easturn Coffee, determining recommendations for competitive strategies and the right business modelto be implemented by Easturn Coffee in order to excel in the competition. In formulating a business model based oncompetitive strategy, the analysis carried out was STEEP analysis and Porter’s Five Forces analysis. Interviews wereconducted with internal parties to obtain research data on business models and business environmental conditions. Theauthor uses qualitative research methods. Data validation uses triangulation of data sources. Based on the analysis thathas been done, it is formulated that the right competitive strategy to be used by Easturn Coffee is differentiation becauseof the competitive advantage it has with small market conditions. Based on the differentiation competitive strategy, a newbusiness model formulation is produced that Easturn Coffee can consider to run its business processes.